Population and health in Latin America and the Caribbean : outstanding matters, new challenges (UN ECLAC SantiagoCL, 2010)
Provides elements of analysis for ECLAC Member States so that they can evaluate the current situation in Latin America and the Caribbean with respect to health, sexual and reproductive health and mortality. Examines the region's accomplishments in the area vis-à-vis the principal agreements, recommendations and goals that are in effect. Identifies the problems that continue to pose challenges, and new challenges they face due to demographic and epidemiological changes in the region as well as the possible consequences of the most recent crises.
Bibliography: p. 109-117.